Timothy Bewes. Free Indirect: The Novel in a Postfictional Age. Columbia U.P., 2022. - Emily Hall (Studies in 20th & 21st Century Literature, 2023)
Review of Timothy Bewes. Free Indirect: The Novel in a Postfictional Age. Columbia U.P., 2022. 315 pp.
Keywords: novel; contemporary; free indirect; discourse; connection; fiction